Maternal Risk Factors for Epilepsy in Children with Cerebral Palsy Attending in Chittagong Medical College Hospital, Chattogram (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Cerebral palsy is a group of disorders that results from nonprogressive interference of the developing brain. It is a major cause of childhood disability in various parts of the world and is often associated with epilepsy and epileptic seizure. Epilepsy has been observed to be more common among children with cerebral palsy which causes additional challenge during their management. Definite risk factors for epilepsy in cerebral palsy have been less high lightened though it is associated with one-third of such patients. The aim of the study was to identify the maternal risk factors of epilepsy in children with cerebral palsy.Materials and methods: This retrospective nested case control study was conducted both in the Outpatient and Inpatient wards of Department of Pediatrics, Chattogram Medical College Hospital, Bangladesh. The study duration was six months from 01.05.2021 to 31.10.2021.Fifty children of cerebral palsy with epilepsy were selected for the case group, and another age matched 50 children of cerebral palsy having no epilepsy were selected for the control group. Data were collected from the hospital records and available family history of both the groups.Results: Majority of the children of both groups belonged to 1-5 years old age group. Spastic quadriplegia in case group and hypotonic in control group were the predominant types of Cerebral Palsy (CP). Generalized tonic and clonic types of seizure were found in majority of the CP patients who had epilepsy. Single associated impairment had a higher prevalence in the control group, but multiple associated impairments were higher in the case group, and the difference was statistically significant. Risk factors that showed significant positive correlation to develop epilepsy in CP were positive family history of epilepsy, history of prolong rupture of membrane, delivery by untrained birth attendant and LSCS as mode of delivery. No statistically significant positive correlation was found between maternal age at delivery, pre and post conceptional maternal diseases and preterm labour as risk factors to develop epilepsy in CP.Conclusion: The study found that apart from family history, history of prolong rupture of membrane, maternal pregnancy related issues including mode of delivery may cause significant impact on children of CP having epilepsy.JCMCTA 2022 ; 33 (2) : 60-65